INTEGRATED MODELS OF DIAMOND FORMATION AND CRATON EVOLUTION - Shirey S.B.; Richardson S.H.; Harris J.W. (My University, 2004)
Two decades of diamond research in southern Africa allow the age, average N content and carbon composition of diamonds, and the dominant paragenesis of their syngenetic silicate and sulfide inclusions to be integrated on a cratonwide scale with a model of craton formation. Individual eclogitic sulfide inclusions in diamonds from the Kimberley area kimberlites, Koffiefontein, Orapa and Jwaneng have Re–Os isotopic ages that range from circa 2.9 Ga to the mid-Proterozoic and display little correspondence with the prominent variations in the P-wave velocity (±1%) that the mantle lithosphere shows at depths within the diamond stability field (150–225 km). Silicate inclusions in diamonds and their host diamond compositions for the above kimberlites, Finsch, Jagersfontein, Roberts Victor, Premier, Venetia, and Letlhakane show a regional relationship to the seismic velocity of the lithosphere. Mantle lithosphere with slower P-wave velocity relative to the craton average correlates with a greater proportion of eclogitic vs. peridotitic silicate inclusions in diamond, a greater incidence of younger Sm–Nd ages of silicate inclusions, a greater proportion of diamonds with lighter C isotopic composition, and a lower percentage of low-N diamonds. The oldest formation ages of diamonds support a model whereby mantle that became part of the continental keel of cratonic nuclei first was created by middle Archean (3.2–3.3 Ga or older) mantle depletion events with high degrees of melting and early harzburgite formation. The predominance of eclogitic sulfide inclusions in the 2.9 Ga age population links late Archean (2.9 Ga) subduction–accretion events to craton stabilization. These events resulted in a widely distributed, late Archean generation of eclogitic diamonds in an amalgamated craton. Subsequent Proterozoic tectonic and magmatic events altered the composition of the continental lithosphere and added new lherzolitic and eclogitic diamonds to the already extensive Archean diamond suite. Similar age/paragenesis systematics are seen for the more limited data sets from the Slave and Siberian cratons.
Keywords: Diamond; Eclogite; Peridotite; Inclusion; P-wave; Craton; Lithosphere